Propionibacterium acnes Enhances the Immunogenicity of HIVBr18 Human Immunodeficiency Virus-1 Vaccine - Teixeira, Daniela; Ishimura, Mayari Eika; Apostólico, Juliana de Souza; Viel, Jacqueline Miyuki; Passarelli, Victor Cabelho; Cunha-Neto, Edecio; Rosa, Daniela Santoro; Longo-Maugéri, Ieda Maria (Frontiers in Immunology, 2018)
Immunization of BALB/c mice with HIVBr18, a DNA vaccine containing eighteen CD4+ T cell epitopes from human immunodeficiency virus (HIV), induced specific CD4+ and CD8+ T cell responses in a broad, polyfunctional and persistent manner. With the aim of increasing the immunogenicity of this vaccine, the effect of Propionibacterium acnes as an adjuvant was evaluated. The adjuvant effects of this bacterium have been extensively demonstrated in both experimental and clinical settings. Herein, administration of two doses of HIVBr18, in the presence of P. acnes, increased the proliferation of HIV-1-specific CD4+ and CD8+ T lymphocytes, the polyfunctional profile of CD4+ T cells, the production of IFN-γ, and the number of recognized vaccine-encoded peptides. One of the bacterial components responsible for most of the adjuvant effects observed was a soluble polysaccharide (PS) extracted from the P. acnes cell wall. Furthermore, within ten weeks after immunization, the proliferation of specific T cells and production of IFN-γ were maintained when the whole bacterium was administered, demonstrating a greater effect on the longevity of the immune response by P. acnes. Even with fewer immunization doses, P. acnes was found to be a potent adjuvant capable of potentiating the effects of the HIVBr18 vaccine. Therefore, P. acnes may be a potential adjuvant to aid this vaccine in inducing immunity or for therapeutic use.